Guitarra Carter 1874 - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N. A. (Zenodo, 2020)
Genus Guitarra Carter, 1874: 210 Syn. Hoplakithara Kirkpatrick, 1907: 285 Pocilloguitarra Topsent, 1928: 45 Type species Guitarra fimbriata Carter, 1874 (type by monotypy). : Published as part of Ekins, Merrick, Erpenbeck, Dirk, Goudie, Lisa & Hooper, John N. A., 2020, New carnivorous sponges and allied species from the Great Australian Bight, pp. 240-266 in Zootaxa 4878 (2) on page 255, DOI: 10.11646/zootaxa.4878.2.2, http://zenodo.org/record/4424977 : {"references": ["Carter, H. J. (1874) Descriptions and Figures of Deep-sea Sponges and their Spicules from the Atlantic Ocean, dredged up on board H. M. S. ' Porcupine', chiefly in 1869; with Figures and Descriptions of some remarkable Spicules from the Agulhas Shoal and Colon, Panama. Annals and Magazine of Natural History, Series 4, 14 (79), 207 - 221, 245 - 257, pls. XIII-XV. https: // doi. org / 10.1080 / 00222937408680964", "Kirkpatrick, R. (1907) Preliminary Report on the Monaxonellida of the National Antarctic Expedition. Annals and Magazine of Natural History, Series 7 (20), 271 - 291. https: // doi. org / 10.1080 / 00222930709487333", "Topsent, E. (1928) Spongiaires de l'Atlantique et de la Mediterranee provenant des croisieres du Prince Albert ler de Monaco. Resultats des campagnes scientifiques accomplies par le Prince Albert I. Monaco, 74, 1 - 376, pls. I-XI."]}